Evaluation of hemodynamic changes during laparoscopic cholecystectomy by transthoracic echocardiography - Arnab Banerjee; Savita Saini; Jatin Lal (Wolters Kluwer Medknow Publications, 2021)
Background and Aims: The purpose of this study was to prospectively examine the effects of pneumoperitoneum and the reverse Trendelenburg position on cardiac hemodynamics during laparoscopic cholecystectomy using transthoracic echocardiography (TTE). Material and Methods: In this prospective observational study, after institutional review board clearance, forty patients of either sex of ASA I-II status undergoing laparoscopic cholecystectomy were enrolled in the study. Changes in cardiac output, stroke volume, and ejection fraction were recorded using TTE at different time intervals: Preoperatively, before creation of pneumoperitoneum, 5 min after creation of pneumoperitoneum, and 5 min after setting the operative reverse Trendelenburg position with legs at the level of the hips. All statistical analyses were performed using the statistical program SPSS version 16 and P value less than 0.05 was considered as statistically significant. Data were examined using mixed analysis of variance (ANOVA) followed by post hoc Bonferroni correction. Results: There was significant fall in cardiac output (CO) (45%, P < 0.001), stroke volume (SV) (42%, P < 0.001), and ejection fraction (EF) (31.8% change, P < 0.001) after creation of pneumoperitoneum with significant rise in MAP (11%, P < 0.001). But with reverse Trendelenburg position, there was a significant improvement of CO (30%), SV (28%), and EF (21% change) in comparison to values after pneumoperitoneum, but still remained below baseline. There was no change in heart rate at different time intervals. There was no significant difference in hemodynamics between ASA I and II patients. Conclusion: Patients undergoing laparoscopic cholecystectomy undergo significant hemodynamic changes after pneumoperitoneum and reverse Trendelenburg position.